2013
DOI: 10.3126/jonmc.v2i1.7664
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Of Portal Vein Pulsatility Pattern And Severity Of Liver Disease In Patients With Cirrhosis And Portal Hypertension

Abstract: Abstract:Objective: To correlate the portal vein pulsatility pattern with severity of liver disease in patients with cirrhosis of liver and portal hypertension. Subjects and methods:Doppler signals from the main portal vein of 36 healthy adults and 52 cirrhotic patients with portal hypertension were studied. Severity of liver disease was graded using modified Child-Pugh classification. Pulsatility of portal flow was quantified using portal venous pulsatility index and complete spectral widening was defined as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 12 publications
(18 reference statements)
4
8
1
Order By: Relevance
“…Mean portal venous velocity is reported to be approximately 15 to 18 cm/sec. 11 the value which we found in our study was 20.4cm/sec, which is almost similar to the reported value. As portal hypertension develops, the flow in the portal vein loses its undulatory pattern and becomes progressively flattened.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Mean portal venous velocity is reported to be approximately 15 to 18 cm/sec. 11 the value which we found in our study was 20.4cm/sec, which is almost similar to the reported value. As portal hypertension develops, the flow in the portal vein loses its undulatory pattern and becomes progressively flattened.…”
Section: Discussionsupporting
confidence: 92%
“…As the severity of portal hypertension increases, flow becomes biphasic and finally hepatofugal. 11 In our patient population we also noted the same finding with 12/20=60% cases having hepatofugal flow pattern in the portal vein.All patients in normal group were found to have 'Fine liver echo texture' with absent ascities and collaterals with hepatopetal flow. Liver echo texture in HCV positive patients was mildly coarse in 3/20 (15 %); coarse in 12/20 (60%) and highly coarse in 5/20 (25%) patients.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…indicated that the pulsatility pattern of portal vein including pulsatility index and complete spectral widening is associated with the grade of liver damage according to Child-Pugh classification among adult patients. [ 7 ] The mean velocity of portal vein flow has been reported to be lower in patients with liver cirrhosis and portal hypertension versus controls[ 8 ] and the same findings were reported among pediatric age groups. [ 9 ]…”
Section: Introductionmentioning
confidence: 83%
“…Patients with severe grades of hepatic encephalopathy (III-IV) as well as those with portal vein thrombosis were excluded from the study. [ 7 ]…”
Section: Methodsmentioning
confidence: 99%